Tibiotalocalcaneal arthrodesis with distal tibial allograft for massive bone deficits in the ankle. Issue 3 (June 2019) - Escudero, Mario I.; Poggio, Daniel; Alvarez, Fernando; Barahona, Maximiliano; Vivar, Diego; Fernandez, Alvaro
Highlights: Tibiotalocalcaneal arthrodesis in patients with severe deformity and bone loss presents a substantial challenge to successful reconstruction. An extensive bone loss in the ankle is mainly due to failed ankle replacement, avascular necrosis, severe trauma and Charcot-neuroarthropathy. The distal tibial structural allograft provides an intimate fit and bony contact. It provides an intrinsic stability to the TTC fusion. The distal tibial structural allograft has lower collapse and fracture rate femoral head allograft. A TTC fusion using distal tibial allograft is a reliable treatment option for patients with an extensive bone defect in the ankle. Abstract: Background: The purpose of this study was to assess the outcomes of distal tibial structural allograft to obtain a stable TTC fusion. Methods: Retrospectively, ten patients were carried out with a minimum one year follow-up. The median age was 72 (33–81). The median BMI was 28 (24–33). Indications for TTC arthrodesis included failed total ankle arthroplasty (n = 7 patients), prior nonunion (n = 2 patients), and a trauma injury. Results: Union rate was 80%. The median initial height of the distal tibial allograft was 19 mm (14–24 mm). In seven cases the allograft did not lose height. The AOFAS score median was 69 (31–84). SF-12 median physical component was 39 (30–53), and 59 (23–62) for mental component. The VAS median was 2 (0–8). Conclusions: TTC using distal tibial allograft shows a lower rate of collapse than other structural grafts and provides a fusion rate higher or in accordance with the literature. Level of evidence: Level IV, retrospective case series.